2020
DOI: 10.1038/s41390-020-01223-6
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease from exposure to secondhand smoke in children in Europe

Abstract: Project "Choosing health priorities and selecting effective interventions to prevent the burden of chronic non-communicable diseases" (http://www.ccmnetwork.it/progetto.jsp?id=node/1977&idP=740); the Ministry of Research and Universities from the Government of Catalonia to EF [grant number 2017SGR319]; the Instituto Carlos III and co-funded by the European Regional Development Fund, FEDER [INT16/00211 and INT17/00103], Government of Spain to EF and the Italian League Against Cancer (Milan) to SG. Disclosure st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…It has been estimated that 20% of pregnant women and 12% of children are regularly exposed to SHS at home in the EU [27], but this also varies widely between countries depending on the prevalence of smoking and the level of enforcement of smoke-free legislation. This is reflected in recent European data on exposure to SHS in restaurants.…”
Section: Tobacco Use In Europe: Facts and Figuresmentioning
confidence: 99%
“…It has been estimated that 20% of pregnant women and 12% of children are regularly exposed to SHS at home in the EU [27], but this also varies widely between countries depending on the prevalence of smoking and the level of enforcement of smoke-free legislation. This is reflected in recent European data on exposure to SHS in restaurants.…”
Section: Tobacco Use In Europe: Facts and Figuresmentioning
confidence: 99%
“…Conversely, ETS exposure in private environments, particularly at home or in cars, cannot be regulated by any smoke-free legislation. Therefore, an unmet need for public health is to study the impact of ETS exposure in domestic ambientes on healthcare, mortality, and social welfare spending [ 5 , 6 , 7 , 8 , 9 ]. Several clinical studies have shown that ETS represents a risk factor for lung cancer [ 10 , 11 ] and induces the release of several cytokines involved in phlogistic processes [ 12 , 13 ], such as inflammatory airway diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental tobacco smoke exposure (TSE) resulting from second-hand smoke (ie, inhalation of emitted smoke) and potentially from third-hand smoke (ie, the uptake of tobacco smoke residuals from polluted surfaces) is known to be a major burden on children's health. [1][2][3] Each year, second-hand smoke is responsible for an estimated 56 000 deaths globally in children younger than 10 years 1 and for 35 633 disability-adjusted life-years among children in the EU. 2 TSE has been linked to various adverse respiratory health outcomes in children, including respiratory tract infec tions, wheezing, and asthma.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Each year, second-hand smoke is responsible for an estimated 56 000 deaths globally in children younger than 10 years 1 and for 35 633 disability-adjusted life-years among children in the EU. 2 TSE has been linked to various adverse respiratory health outcomes in children, including respiratory tract infec tions, wheezing, and asthma. 4,5 Governmental action to protect children from these deleterious effects of TSE is urgently needed, given that children are not able to control their degree of exposure.…”
Section: Introductionmentioning
confidence: 99%